Performatism, or the end of postmodernism (American Beauty) - Raoul Eshelman (Przestrzenie Teorii)
The presented text is a translation of the first chapter of Eshelman’s book Performatism, or the End of Postmodernism (2008). Its main thesis is based on the assumption that along with the exhaustion of postmodernism a new aesthetic paradigm emerges, namely – performatism. Deriving his project from a new notion of sign (grounded on the anthropological theory of ostensivity by Eric Gans) and the description of a crucial aesthetic device called ‘double framing’, Eshelman tracks down symptoms of the epochal change in literary and visual works as well as in movies and architecture. The text also lays foundation for new monist concepts of subjectivity, time and history.